Pendekatan Psikologi dalam Studi Islam dan Kontribusinya terhadap Studi Keislaman di Indonesia - Joni Putra; Jihan Ramadhan; Rima Yuni Saputri (CV. Creative Tugu Pena, 2024)
This article aims to determine the implementation of psychological preaching in Islamic studies and its contribution to Islamic studies in Indonesia. The psychological approach in Islamic studies has a significant role in explaining the physical symptoms of each human individual. This research uses the library research method, namely the library method by studying books, journals and relevant sources. The data analysis uses descriptive analysis by reducing data, presenting data, and finally conclusions. The results of this research show that a psychological approach to Islamic studies is one answer in making it easier to understand Islamic studies well, the object of study is the symptoms and souls of religious humans, which will appear in the form of attitudes, behavior and behavior. Apart from that, how can humans have a good relationship with God and with each other. The approach is taken through 3 aspects, namely; 1) structural approach, 2) functional approach, and 3) psycho-analytic approach. Keywords : Islamic Studies, Islamic Contribution, Psychological Preaching